2011
DOI: 10.1097/inf.0b013e318204dcf3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of First Urinary Tract Infection With Fever in Children

Abstract: Girls represent 63% of cases with first UTI. For 91% of UTIs, Escherichia coli is held responsible with a high rate of resistance to ampicillin and trimethoprim/sulfamethoxazole. US is an excellent screening tool that allows avoidance of unjustified voiding cystourethrography studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 25 publications
(22 reference statements)
4
36
0
13
Order By: Relevance
“…We performed 21 MCUG and7 patent (33.3%) has vesicoureteral reflux (VUR) Grade 3 to Grade 5 refluxes, which is in agreement with the findings of previous studies. 20,21 This study shown that it is highly recommended that children with recurrent UTI should undergo RUS and MCUG for early detected of complication and prevention of severe complication like renal scar.…”
Section: Discussionmentioning
confidence: 93%
“…We performed 21 MCUG and7 patent (33.3%) has vesicoureteral reflux (VUR) Grade 3 to Grade 5 refluxes, which is in agreement with the findings of previous studies. 20,21 This study shown that it is highly recommended that children with recurrent UTI should undergo RUS and MCUG for early detected of complication and prevention of severe complication like renal scar.…”
Section: Discussionmentioning
confidence: 93%
“…It is one of the commonest bacterial infection in children especially in those less than 5 years old. As per ISPN guidelines UTI is more common in males during infancy and there is female preponderance thereafter [1][2][3]. Taneja et al in their study of 143 infants with culture positive UTI, found male preponderance, with 116 being males and 27 females [3].…”
Section: Discussionmentioning
confidence: 99%
“…Other less common pathogens found in present study were Staphylococcus species 21(11%) Pseudomonas species 11(6%), and Proteus species 6(3%). Their prevalence is variable in other studies as well (Foxman, 2014;Ismaili et al, 2011).…”
Section: Fig1 Distribution Of Organisms Isolatedmentioning
confidence: 90%
“…Samples were cultured on blood agar and MacConkey agar by using semiquantitative method of culture. Diagnosis of UTI was made by means of positive urine culture (colony count > or = 100000CFU/ml of urine (Ismaili et al, 2011). Organisms were identified by morphology and biochemical reactions.…”
Section: Methodsmentioning
confidence: 99%